Relationship between the nucleolar cycle and chromatoid body formation in the spermatogenesis of Phrynops geoffroanus (Reptilia Testudines) - Peruquetti, Rita L. [UNESP]; Taboga, Sebastiao R. [UNESP]; Cabral, Silvia Rosana Pagliarini [UNESP]; Oliveira, Classius de [UNESP]; Oliveira, Maria Tercília Vilela de Azeredo [UNESP] (Taylor & Francis Ltd, 2012)
The nucleolus is a distinct nuclear territory involved in the compartmentalization of nuclear functions. There is some evidence of a relationship between nuclear fragmentation during spermatogenesis and chromatoid body (CB) formation. The CB is a typical cytoplasmic organelle of haploid germ cells, and is involved in RNA and protein accumulation for later germ-cell differentiation. The goal of this study was to qualitatively and quantitatively describe the nucleolar cycle during the spermatogenesis of Phrynops geoffroanus (Reptilia Testudines), and compare this nucleolar fragmentation with CB formation in this species through the use of cytochemical and ultrastructural analysis. Qualitative analysis showed a fragmentation of the nuclear material after pachytene of the first meiotic division in the primary spermatocytes. Quantitative analysis of the nucleolar cycle revealed a significant difference in the number of nucleoli and in the size of the nucleolus between spermatogonia and early spermatids. Using ultrastructural analysis, we recorded the beginning of the CB formation process in the cytoplasm of primary spermatocytes at the same time as when nuclear fragmentation occurs. In the cytoplasm of primary spermatocytes, the CB was observed in association with mitochondrial aggregates and the Golgi complex. In the cytoplasm of early spermatids, the CB was observed in association with lipid droplets. In conclusion, our data show that the nucleolus plays a role in the CB formation process. During spermatogenesis of P. geoffroanus, the CB is involved in some important biological processes, including acrosome formation and mitochondrial migration to the spermatozoon tail and middle piece region.
Keywords: Nucleolar cycle; Spermatogenesis; Chromatoid body; reptiles